Analisis Konsep Pembelajaran Alquran dengan Metode Iqra: Suatu Kajian Literatur - Tito Erliando Saputra; Alvin Ardiansyah Putra; Gusmaneli Gusmaneli (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The Quran is the word of Allah revealed to Prophet Muhammad (SAW) through the angel Gabriel to serve as a guide for humanity. All human beings are required to believe in and study the Quran, one of the methods being Iqra. The Iqra method emphasizes fluent reading without spelling. This method was first taught by K.H. As’ad Humam in 1983. It is based on a child-centered approach, providing students with ample opportunities to develop optimally according to their abilities.This study will discuss the definition of the Iqra method, its history, advantages and disadvantages, as well as a comparison with other methods of Quran study, in order to identify the most effective way to learn the Quran. With this method, children can read the Quran properly according to the rules of Tajwid, including aspects such as makhraj al-huruf, mad, idgham, and other reading laws.